2002
DOI: 10.1136/oem.59.9.625
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bisphenol A and plasma hormone concentrations in male workers exposed to bisphenol A diglycidyl ether and mixed organic solvents

Abstract: Aims: To evaluate effects of exposure to bisphenol A diglycidyl ether (BADGE) on urinary excretion of bisphenol A, and plasma gonadotrophic hormones and testosterone in male epoxy resin sprayers. Methods: Cross sectional study of 42 workers whose job was to spray epoxy resin hardening agents including BADGE and mixed organic solvents, and 42 matched control workers without BADGE use in the same machine plants.Results: Concentrations of urinary bisphenol A were higher in the epoxy resin sprayers (median 1.06 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(106 citation statements)
references
References 28 publications
3
100
2
1
Order By: Relevance
“…We found only one public report on urinary BPA levels of workers occupationally exposed to BPA 16) . The participants in that study were 42 male workers, whose job task was to spray BPA diglycidyl ether (BADGE) with mixed organic solvents as an epoxy resin hardening agent in a machine plant and two related plants.…”
Section: Discussionmentioning
confidence: 83%
“…We found only one public report on urinary BPA levels of workers occupationally exposed to BPA 16) . The participants in that study were 42 male workers, whose job task was to spray BPA diglycidyl ether (BADGE) with mixed organic solvents as an epoxy resin hardening agent in a machine plant and two related plants.…”
Section: Discussionmentioning
confidence: 83%
“…It has also been shown that BADGE generates BPA endogenously in BADGE-exposed male workers and that their plasma FSH levels decrease as their BPA levels rise. Nonetheless, neither free testosterone nor LH levels are affected in these conditions (Hanaoka et al, 2002). In male partners of pregnant women, urinary BPA levels have been inversely associated only with the free androgen index (FAI: testosterone/SHBG; sex hormone-binding globulin; Mendiola et al, 2010).…”
Section: Inhibin Bmentioning
confidence: 99%
“…(European-Union, 2003). One study measured total urinary bisphenol A in Japanese workers who sprayed an epoxy compound (Hanaoka et al, 2002). …”
Section: Summary Of Human Exposurementioning
confidence: 99%
“…Hanaoka et al (2002), supported by the Japanese Ministry of Health and Welfare and Ministry of Education, Science, Sports, and Culture, examined possible relationships between bisphenol A exposure and hormone levels in male workers. Exposed workers included 42 men in 3 Japanese plants who sprayed an epoxy hardening agent consisting of a mixture of bisphenol A diglycidyl ether (10-30%), toluene (0-30%), xylene (0-20%), 2-ethoxyethanol (0-20%), 2-butoxyethanol (0-20%), and methyl isobutyl ketone (0-30%).…”
Section: Experimental Animal Studies Considered Bymentioning
confidence: 99%
See 1 more Smart Citation